2018
DOI: 10.3389/fvets.2018.00150
|View full text |Cite
|
Sign up to set email alerts
|

Pooled Platelet-Rich Plasma Lysate Therapy Increases Synoviocyte Proliferation and Hyaluronic Acid Production While Protecting Chondrocytes From Synoviocyte-Derived Inflammatory Mediators

Abstract: Platelet-rich plasma (PRP) preparations are being used with moderate success to treat osteoarthritis (OA) in humans and in veterinary species. Such preparations are hindered, however, by being autologous in nature and subject to tremendous patient and processing variability. For this reason, there has been increasing interest in the use of platelet lysate preparations instead of traditional PRP. Platelet lysate preparations are acellular, thereby reducing concerns over immunogenicity, and contain high concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 79 publications
(59 reference statements)
3
53
0
Order By: Relevance
“…Likewise, studies describing cell types derived from other tissues in the knee also report on increased proliferation. 16,35,[39][40][41] It is important to highlight our study found increased proliferation only in the case where 20% PRP was added to the culture medium. Growth factor concentrations in this experimental condition are most likely much higher than when PRP is used in a clinical setting for intra-articular injections.…”
Section: Discussionmentioning
confidence: 58%
“…Likewise, studies describing cell types derived from other tissues in the knee also report on increased proliferation. 16,35,[39][40][41] It is important to highlight our study found increased proliferation only in the case where 20% PRP was added to the culture medium. Growth factor concentrations in this experimental condition are most likely much higher than when PRP is used in a clinical setting for intra-articular injections.…”
Section: Discussionmentioning
confidence: 58%
“…The application of PRP also may restore joint lubrication through several mechanisms. First, it has a stimulating effect on the chondrocytes and synoviocytes, due to the fact that it not only enhances its proliferation but also increases the production of hyaluronic acid, improving the lubricating capacity of the synovial fluid [66][67][68]. Secondly, PRP also influences lubrication through the superficial zone protein (SZP) or lubricin.…”
Section: Biolubricanting Effectmentioning
confidence: 99%
“…In any case, the identification of PRPderived anabolic growth factors (basic FGF, TGF-β1, TGF-β2, EGF, IGF-I, PDGF-AB, PDGF-BB, VEGF) and anti-inflammatory cytokines (IL-1ra, sTNF-R1, sTNF-RII, IL-4, IL-10, IL-13, IFNγ) may present therapeutic potential in the treatment of osteoarthritis, especially in combination with MSCs, through enhancing or preserving their regenerative properties [23][24][25]. In addition, a positive effect on joint lubrication through stimulation of synoviocytes-derived hyaluronic acid has been reported for PRP, thus, when administered as co-adjuvant of MSCs, PRP could increase the intra-articular retention and survival of MSCs in an anti-inflammatory environment [26,27].…”
Section: Introductionmentioning
confidence: 99%